Christian Perspectives on Legal Thought - McConnell, Michael W.; Cochran, Robert F.; Carmella, Angela C. (Yale University Press, 2001)
Intro -- Contents -- Foreword -- Acknowledgments -- Introduction -- Part One Christian Perspectives on Schools of Legal Thought -- Section 1 Enlightenment Liberalism -- Old Liberalism, New Liberalism, and People of Faith -- Liberal Hegemony and Religious Resistance: An Essay on Legal Theory -- Christianity and the Roots of Liberalism -- The Earthly Peace of the Liberal Republic -- Section 2 Legal Realism -- A Century of Skepticism -- Section 3 Critical Legal Studies -- Law and Belief: Critical Legal Studies and Philosophy of the Law-Idea -- Section 4 Critical Race Theory -- What's Love Got to Do with It? Race Relations and the Second Great Commandment -- Reinhold Niebuhr and Critical Race Theory -- Hispanics, Catholicism, and the Legal Academy -- Section 5 Feminism -- Independence or Interdependence? A Christian Response to Liberal Feminists -- Citizen-Soldiers Are Like Priests: Feminism in Law and Theology -- Section 6 Law and Economics -- Law and Economics: An Apologia -- A Catholic Social Teaching Critique of Law and Economics -- Part Two Christian Traditions and the Law -- Christian Traditions, Culture, and Law -- Section 1 Synthesists: Reconciling Christ and Law -- A Catholic View of Law and Justice -- Natural Law -- Section 2 Conversionists: Christ Transforming Law -- The Calvinist Paradox of Distrust and Hope at the Constitutional Convention -- A Calvinist Perspective on the Place of Faith in Legal Scholarship -- Section 3 Critical Legal Studies -- The Radical Reformation and the Jurisprudence of Forgiveness -- "Incendiaries of Commonwealths": Baptists and Law -- On Liberty and Life in Babylon: A Pilgrim's Pragmatic Proposal -- Section 4 Dualists: Christ and Law in Tension -- A House Divided? Anabaptist and Lutheran Perspectives on the -- Making Our Home in the Works of God: Lutherans on the Civil Use of the Law.